The impact of physical exercise on neuroinflammation mechanism in Alzheimer’s disease - Hu, Junhui; Huang, Baiqing; Chen, Kang (Frontiers in Aging Neuroscience, 2024)
Alzheimer's disease (AD) is a principal cause of dementia worldwide, significantly impacting societal and personal costs. This review consolidates findings from recent studies on physical exercise as a nonpharmacological intervention to modulate neuroinflammation and enhance neuronal function in AD. Reviews indicate that regular physical exercise modifies neuroinflammatory pathways, improves cognitive function, and promotes brain health in AD patients. It positively affects microglial and astrocytic activation states, reinforces blood-brain barrier integrity, and reduces AD-related gut inflammation. These mechanisms are linked to notable improvements in cognitive metrics and brain health biomarkers, advocating for the integration of exercise into comprehensive AD management strategies. Highlighting the need for ongoing research, this review calls for refining exercise regimens to optimize their long-term benefits in slowing AD progression.